THE EFFECTIVENESS OF ASEAN ECONOMIC COMMUNITY - Sumitro Sumitro (Jurnal Informatika, 2015)
Free trade agreement of ASEAN Economic Community (AEC) immediately will be implementedin the region. The four pillars of the AEC concept is a reference in the enforcement process. All memberstates have made preparations including Indonesia. Small and Medium-sized Enterprises also makepreparations. The preparation of the Indonesian government in the deal and how the measures taken toprotect Small and Medium-sized Enterprises is a discussion in the review of this article. Policies madeby the government, including the measures taken for businesses Small and Medium-sized Enterprises,still found some difficulties in implementation.Because entirely not going well then the nomination acceleration trade policies comprehensivelyneeds to be activated immediately so that the various policy papers that the government made will be ableto work together with entreperenurs. This study also found unrediness of national products, especiallySmall and Medium-sized Enterprises in competing due to human resources, inadequate infrastructureand the investment climate.